2010
DOI: 10.1007/s00442-010-1810-2
|View full text |Cite
|
Sign up to set email alerts
|

Does personality in small rodents vary depending on population density?

Abstract: Personality means an individual's unique way of behaving and reacting to the environment. It is a stable and heritable trait, which is expressed consistently in different situations. The aim of our study was to develop novel tests to depict the personality structure of the bank vole Myodes glareolus, and to determine if the phase of the population cycle, i.e. population density, affects personality. We focused on some central aspects of bank vole behaviour: mobility, risk taking, exploratory behaviour, dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…Explanation for this is probably the infanticidal males' proneness to take more risks and direct movements also into the new unknown areas compared to noninfanticidal males moving more in the familiar environment. Korpela et al (2011) found relatively high correlation between male infanticide and novelty-seeking behavior in a personality study conducted in laboratory but using wild-caught voles. Dominant males are found to be more often infanticidal against unrelated pups in laboratory mice (Mus musculus) (Vom Saal and Howard 1982;Huck 1984), but the picture with free living voles is not so clear.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Explanation for this is probably the infanticidal males' proneness to take more risks and direct movements also into the new unknown areas compared to noninfanticidal males moving more in the familiar environment. Korpela et al (2011) found relatively high correlation between male infanticide and novelty-seeking behavior in a personality study conducted in laboratory but using wild-caught voles. Dominant males are found to be more often infanticidal against unrelated pups in laboratory mice (Mus musculus) (Vom Saal and Howard 1982;Huck 1984), but the picture with free living voles is not so clear.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, we do not expect any difference in female behavior due to the infanticide treatment, but habitat fragmentation may decrease female movement area size. Infanticidal males have shown to be more aggressive in laboratory (Vihervaara et al 2010) and shown more novelty-seeking behavior (Korpela et al 2011) which are expected to lead to higher activity also in the field.…”
Section: Introductionmentioning
confidence: 97%
“…However, like shown before (Korpela et al 2011) infanticidal males were more active in moving around and seeking the vicinity of the boxes than the non-infanticidal ones. Korpela et al (2011) showed that the infanticidal males are more bold in personality traits than the non-infanticidal conspecifics (Korpela et al 2010) and in field studies infanticidal males are more active and move over larger distances than non-infanticidal ones (Haapakoski et al 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Korpela et al (2011) showed that the infanticidal males are more bold in personality traits than the non-infanticidal conspecifics (Korpela et al 2010) and in field studies infanticidal males are more active and move over larger distances than non-infanticidal ones (Haapakoski et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation